APAKAH PENGUNGKAPAN MANAJEMEN RISIKO PERUSAHAAN MEMENGARUHI NILAI PERUSAHAAN? STUDI PADA PERUSAHAAN YANG TERCATAT DI INDEKS KOMPAS100: DOES DISCLOSURE OF ENTERPRISE RISK MANAGEMENT AFFECT COMPANY VALUE? STUDY ON COMPANIES LISTED ON THE KOMPAS100 INDEX - Miftahul Zannah; Suherman Suherman; Destria Kurnianti (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This study aims to determine the effect of disclosure of company risk management on company value in companies listed on the Kompas100 Index from 2018 to 2021. Using purposive sampling, the samples obtained in this study were 292 observations. Data were collected through financial reports and annual reports, then panel data regression was performed with Eviews 12 econometric software. The results found from the research sample indicate that disclosure of company risk management has a significant positive effect on firm value